STUDY OF MORPHOLOGICAL CHANGES IN WHITE BLOOD CELLS OF A HUMAN CADAVER FOR ESTIMATION OF POST MORTEM INTERVAL - Anand, Aditya; Chandra, Vikash; Sharma, Mukul (Journal of Forensic Medicine and Toxicology, 2023)
Estimation of post-mortem interval plays a crucial role in the death investigation and to find out the approximate time of death. Along with traditional methods, entomology and biochemical changes in blood, CSF, and intraocular fluids are studied to estimate the post-mortem interval (PMI) more accurately. The study of morphological changes in White Blood Cells (WBC) is relatively unexplored. A descriptive cross-sectional study was planned to study the post-mortem changes in the morphology of WBCs of human cadavers kept in cold storage with known postmortem intervals. The present study included a total of 210 cases irrespective of sex. We found that eosinophils and monocytes were most susceptible to autolysis, followed by neutrophils. Lymphocytes were the most resistant WBC. No WBC was found intact beyond 72 hours of post-mortem interval. The study of morphological changes in blood cells of human corpses gives some idea of post-mortem interval.
Keywords: Postmortem interval; postmortem changes; white blood cell; morphological changes